The crime of aggression, humanity, and the soldier - Dannenbaum, Tom (Cambridge : Cambridge University Press, 2018)
The international criminality of waging illegal war, alongside only a few of the gravest human wrongs, is rooted not in its violation of sovereignty, but in the large-scale killing war entails. Yet when soldiers refuse to kill in illegal wars, nothing shields them from criminal sanction for that refusal. This seeming paradox in law demands explanation. Just as soldiers have no right not to kill in criminal wars, the death and suffering inflicted on them when they fight against aggression has been excluded repeatedly from the calculation of post-war reparations, whether monetary or symbolic. This, too, is jarring in an era of international law infused with human rights principles. Tom Dannenbaum explores these ambiguities and paradoxes, and argues for institutional reforms through which the law would better respect the rights and responsibilities of soldiers.
Introduction -- The criminalization of aggression and the putative dissonance of the law's treatment of soldiers -- Soldiers and the crime of aggression: required to kill for a criminal end, forgotten in wrongful death -- The criminalization of aggression -- The duty to disobey illegal orders -- The law of being forced to kill in a wrongful war -- Victims' participation and reparations -- The human stakes: moral and physical wounds -- Normative reasoning and international law on aggression -- What it means to offer a normative account -- The realist objection -- Why the legal status of soldiers' wounds matters -- What is criminally wrongful about aggressive war? -- The orthodox account: the moral value of states -- The wrong of criminal aggression: unjustified killing and violence -- Two possible problem cases for the unjustified killing account -- What this means for the soldier -- Can international law's posture towards soldiers be defended? -- Military duress -- Duress and culpability -- Answering the wrong question: moral perspectives -- The tragedy of deaths on both sides -- Shedding certain blood for uncertain reasons -- Invincible ignorance and the fog of criminal war -- A spectrum of uncertainty -- The normative vincibility of ignorance -- Why uncertainty mandates restraint -- The structure of the jus ad bellum -- Deference -- The implications of the vincibility of ignorance -- Legal spheres and hierarchies of obligation -- Political deference and international crime -- Associative ties and the responsibility to protect -- The myth of an aggressive moment -- Revising the invincible ignorance account -- Conflicting obligations and the right to do the right thing -- Civilian control of the military -- Political obligation, associative duties, and reparations -- Understanding the warrior's code -- The war convention and mitigating the hell of war -- The normative force of convention -- The warrior's code and combatant reparations -- The warrior's code and immunity vs. non-culpability -- A jus ad bellum crime of appropriately narrow scope -- Global norms, domestic institutions, and the military role -- Obedience and military functioning -- The question of interpretive authority -- Military functioning and soldiers making evaluative decisions -- International law, global human security, and military competence -- The enduring culpability of obedient participation in illegal wars -- The necessity of enforced culpability -- Necessity and victim status -- Respecting soldiers in institutions and doctrine: the internal imperative to reform -- Shifting contingencies -- Remotely fought or low-risk wars -- The rise of private contractors -- The timing of disobedience protection -- The contingency of necessity -- Victim status -- Domestic implications -- The domestic significance of the jus ad bellum -- Deference and the value of a devil's advocate -- A limited right to disobey orders to fight in illegal wars -- Reflecting on why we fought: institutionalizing the post-war commission of inquiry -- Unlawful but justified -- Evaluating reform -- An internal normative vision for international reform -- From deserter to refugee -- The jus ad bellum and the human rights of rights defenders -- The crime of aggression and the soldier's right to life -- Conclusion.
Title from publisher's bibliographic system (viewed on 27 Apr 2018).
Keywords: Aggression (International law); Soldiers -- Legal status, laws, etc